Gastrosplenocolic fistula secondary to non-Hodgkin B-cell lymphoma. Issue 1 (13th January 2020) - Yokoyama, Yujiro; Kashyap, Sarang; Ewing, Edward; Bloch, Robert
Abstract: Gastrocolic fistula (GSF) is a rare entity that arises mainly from splenic or gastric lymphoma. Gastric and splenic lymphomas can also fistulate with other organs, including the pleura and the colon, but there has been no reported case to best of our knowledge of a fistula involving three different organs. We hereby present the case of a female patient with gastrosplenocolic fistula secondary to non-Hodgkin B-cell lymphoma. We performed an en bloc partial gastrectomy with splenectomy and partial left colon resection with colostomy. GSF can be treated with chemotherapy. However, when the definite diagnosis is unclear or GSF is causing serious complications such as bleeding or active infection, we believe surgical excision is the treatment of choice.